Glycemic response of poultries in different feeding systems - Marcos Martinez do Vale; Daniela Regina Klein; Tatiane Branco; Mauricio Portella dos Santos (Acta Scientiarum. Animal Sciences, 2019)
The management of poultry feed is an important welfare promoter and the glycemic index a noninvasive evaluation. The aim was to evaluate the glycemic response of broiler breeders in restricted feeding system, and broilers receiving ad libitum feeding. Two experiments were carried out: I) 39-week-oldbroiler breeders, fed with three sources of fiber, in a completely randomized design in factorial scheme (3 fiber diets x 7 collection periods); and II) broilers, 42 days old, housed in different light systems, in a completely randomized design in factorial design (2 sexes x 2 lighting conditions x 13 collection periods). Blood glucose levels were measured at random collecting one blood drop from foot, with three replicates in each condition and treatment. In broiler breeder different fiber sources had no effect on glycemia, but the period affected circulating glucose levels, presenting a minimum of 184.3 mg dL-1 before feed and, a maximum of 242.5 mg dL-1 four hours after feeding. In broilers, there was a significant effect in glycemia for collection period and for sex, and interaction between lighting conditions and collection period. Further studies are needed to establish reference values to compare blood glucose levels in poultry.